Translation Teaching Strategies For Arabic Language Education Students at The State Islamic Institute (IAIN) Ponorogo - Amir Mukminin (IAIN Kediri, 2020)
This study aims to explore teaching methods and strategies in teaching translation among lecturers at IAIN Ponorogo. In their teaching, the lecturers determine the high goals, that is being able to translate Arabic into Indonesian, and the reverse; However, students' language competence is not good enough to achieve that goal because translation is a work that must be supported by various types of competencies such as understanding text, understanding Arabic grammar, understanding methods and translation strategies, and so on. Student competencies are not in accordance with the specific goals in this education, and this fact is what leads lecturers to carry out effective teaching and use good types of teaching methods and strategies so that education is successful and students can achieve the goals. Researchers used a qualitative approach and explored descriptive facts such as written voices or individual speeches, contemplative traits and data sources. The data analysis method is descriptive analysis with three methods, namely data reduction and data presentation. The results of this study are 1) The method used in teaching translation: translation is word by word, because translation is done between separation by placing the translation under the source language in order to maintain word order. The word is translated as a word in a general sense. Pro translation because it produces contextual meaning of the source language into the target language appropriately. Therefore, translators are careful in translating cultural vocabulary and adjusting grammar. This method seeks to achieve the author's goals. 2) The strategy used is an expansion against the target, and the word element is an expansion in the target language, semantic translation, ordinal translation, transcription or semantic translation intersection. 3) And the learning outcomes obtained by students are good, academic results are not good. The result of the equation 70 (seventy)Â